2015
DOI: 10.3109/21678421.2015.1074702
|View full text |Cite
|
Sign up to set email alerts
|

Curable or treatable? The implications of different definitions of illness when treating patients suffering from amyotrophic lateral sclerosis

Abstract: People suffering from amyotrophic lateral sclerosis (ALS) have complex health and care needs. The purpose of this study was to gain insight into the gaps in the health and community service care provided to ALS patients. In order to ensure continuity of care, specialist centres have to build effective relationships with local primary health care services and community services, health managers, physicians, patients, families and the surrounding support networks. We undertook a qualitative study that examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…In line with previous research, we found that nursing assistants struggled with lack of community in the home-based setting (Ahlstr€ om & Wadensten 2010, Christensen 2012. Limited knowledge among primary healthcare professionals may be a key reason why families are wary of MND care provision (Brown et al 2005, Hughes et al 2005, Cappellato et al 2015. One of the most advanced tasks in primary healthcare is providing respiratory support, often occurring in late-stage MND (Dybwik et al 2011(Dybwik et al , 2012.…”
Section: Mnd and Service Provisionsupporting
confidence: 83%
See 3 more Smart Citations
“…In line with previous research, we found that nursing assistants struggled with lack of community in the home-based setting (Ahlstr€ om & Wadensten 2010, Christensen 2012. Limited knowledge among primary healthcare professionals may be a key reason why families are wary of MND care provision (Brown et al 2005, Hughes et al 2005, Cappellato et al 2015. One of the most advanced tasks in primary healthcare is providing respiratory support, often occurring in late-stage MND (Dybwik et al 2011(Dybwik et al , 2012.…”
Section: Mnd and Service Provisionsupporting
confidence: 83%
“…, Cappellato et al . ). One of the most advanced tasks in primary healthcare is providing respiratory support, often occurring in late‐stage MND (Dybwik et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The absence of precise guidelines regarding essential levels of care and the autonomy granted to the Regional authorities and other institutional actors at local level have led to a fragmentation of the services and a lack of co‐ordination in the management of ALS in Italy (Cappellato, Bosco, Chio, & Calvo, ). With conditions as complex as ALS, one of the primary issues concerns the difficulty of identifying a figure capable of co‐ordinating and combining the interventions to ensure continuity of care at all stages of the disease.…”
Section: Introductionmentioning
confidence: 99%